2019
DOI: 10.15405/epsbs.2019.11.39
|View full text |Cite
|
Sign up to set email alerts
|

The Importance Of Emotions And Personal Characteristics On Adolescents’ Risky Photo-Disclosure Online

Abstract: Researchers state that adolescents are likely to engage in risky photo disclosure online, which might be related to their emotions and personal characteristics. Research Questions: How positive and negative emotions when sharing risky photos online are related to adolescents' risky photo disclosure online? How important personal characteristics are related to adolescents' risky photo disclosure online? The purpose of this study is to find out how positive and negative emotions are related to adolescents' tende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In addition, cyberbullying (disclosure of personal information, watching pornographic and aggressive content, receiving unacceptable text messages with sexual content, etc. ), which causes painful consequences for children (Grigutytė, et al, 2019), and sharing explicit photos in order to obtain a positive evaluation (Paluckaitė & Žardeckaitė-Matulaitienė, 2019). Risky behaviour, as a phenomenon typical to adolescence, increases the likelihood of exposure to hazards and risks that are greater at this stage of life (O'Reilly et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, cyberbullying (disclosure of personal information, watching pornographic and aggressive content, receiving unacceptable text messages with sexual content, etc. ), which causes painful consequences for children (Grigutytė, et al, 2019), and sharing explicit photos in order to obtain a positive evaluation (Paluckaitė & Žardeckaitė-Matulaitienė, 2019). Risky behaviour, as a phenomenon typical to adolescence, increases the likelihood of exposure to hazards and risks that are greater at this stage of life (O'Reilly et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that girls spend more time communicating on OSN social networks than boys, and therefore their communication on OSN can often lead to greater vulnerability regarding aspects such as harassment, bullying, exploitation, sexual persecution, and seduction (Dowdell & Bradley, 2010). Girls are more likely to post explicit photos on social networks (Ramsey & Horan, 2018;Paluckaitė et al, 2019), and they more often share information about their daily activities with others (Wiliams & Merten, 2009).…”
Section: Introductionmentioning
confidence: 99%